Promising rice hybrids in Bay Islands - Mandal, Asit B.; Elanchezhian, R. (Indian Farming, 2016)
The present article sums up the immense prospect of rice hybridseven in the remote union territory of Andaman and Nicobar Islands. It is expected that cultivation of productive premium quality hybridrice would substantially contribute in enhancing the rice productivity and production thereof to avert fallout in the production requirement of rice in Andaman and Nicobar Islands in the days to come.